Carbon dioxide catalytic conversion catalytic material, preparation method thereof and carbon dioxide catalytic conversion method
Patent Information
- Application Number
- CN202211307028.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-25
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2042-10-25
AI Technical Summary
但贵金属成本高昂,不利于大规模应用,且该反应仍需要在高压下进行
[0035] 1. No highly toxic organic solvents are required, and the preparation method is simple and environmentally friendly;
Smart Images

Figure BDA0003906239490000091 
Figure HDA0003906239500000011 
Figure HDA0003906239500000012
Abstract
Description
Technical Field
[0001] This invention belongs to the field of carbon dioxide catalytic conversion, specifically relating to a porous copper-modified indium oxide material for carbon dioxide catalytic conversion, its preparation method, and a carbon dioxide catalytic conversion method. Background Technology
[0002] With the continuous development of the economy and society, the energy and environmental crisis is intensifying. Developing efficient carbon dioxide catalytic conversion technologies has gradually become one of the key technologies for promoting "carbon peaking and carbon neutrality." Utilizing catalysis to convert CO2 into high-value-added chemicals such as methanol, methane, and carbon monoxide has significant theoretical and practical implications. However, the thermodynamic stability of CO2 molecules and their difficulty in activation greatly limit the improvement of their reaction efficiency. The key to solving this problem lies in the design and construction of catalysts. Currently, commonly used catalytic conversion pathways mainly include thermocatalysis, photocatalysis, and electrocatalysis. Typical catalyst systems include Cu-based catalysts, noble metal catalysts, In2O3-based catalysts, and novel semiconductor materials. Among these, photocatalysis can directly utilize solar energy to activate carbon dioxide molecules, but its efficiency is low and difficult to achieve large-scale application; while traditional thermocatalytic methods have high energy consumption, and their efficiency needs further improvement.
[0003] Patent CN110479235A discloses an indium oxide catalyst, its preparation method, and its application. The catalyst is a hexagonal indium oxide with a nano-hierarchical structure, and it is used in the reaction of carbon dioxide hydrogenation to produce methanol. However, this system requires operation under high pressure above 1 MPa, which is highly dangerous and energy-intensive.
[0004] Patent CN114405505A relates to a platinum-modified indium-based oxide catalyst, its preparation method, and its application. The catalyst mainly consists of the noble metal active component Pt and the oxide support In₂O₃. Using a Pt / In₂O₃ composite catalyst is beneficial for improving the activity of the carbon dioxide hydrogenation reaction and can be applied under high pressure in the synthesis of methanol from carbon dioxide. However, the high cost of noble metals hinders large-scale application, and the reaction still requires high pressure. Summary of the Invention
[0005] The first technical problem to be solved by the present invention is to provide a CO2 conversion method that addresses the aforementioned problems in the prior art, and that can carry out CO2 catalytic conversion under relatively low pressure.
[0006] The second technical problem to be solved by the present invention is to provide a catalytic material for the above-mentioned catalytic conversion of carbon dioxide and a method for preparing the same.
[0007] This invention provides a catalytic material for the catalytic conversion of carbon dioxide, which is a porous copper-modified indium oxide material, comprising indium oxide and doped copper elements, and has a rich micro-mesoporous structure.
[0008] The catalytic material has an abundant microporous structure, wherein the micropore volume can be 0.005–0.03 cm³. 3 ·g –1 For example, 0.01~0.02cm 3 ·g –1 Mesopore volume: 0.1–0.4 cm³ 3 ·g –1 For example, 0.15–0.35 cm 3 ·g –1 .
[0009] In one embodiment, the catalytic material has micropores with a pore size (diameter) of 1-5 nm.
[0010] In the catalytic material used for carbon dioxide catalytic conversion, copper is highly dispersed in the indium oxide lattice framework in a doped form. The dispersion of copper can be observed using aberration-corrected electron microscopy.
[0011] In the catalytic material, the copper content is preferably 0.5 to 8% by weight, for example, 1 to 5% by weight.
[0012] In the catalytic material, the indium oxide content can be 92-99.5% by weight, for example, 95-99% by weight.
[0013] A method for preparing a catalytic material for carbon dioxide catalytic conversion includes the following steps:
[0014] S1. After uniformly dispersing the indium salt in the solvent, a copper-containing precursor is added to obtain mixture A;
[0015] S2. Prepare a mixed dispersion B of surfactant and alkali;
[0016] S3. Under constant temperature conditions, add the mixed dispersion B to the mixture A, and adjust the pH of the resulting mixture to 11-13.
[0017] S4. React fully under constant temperature, then separate the product, wash and dry the separated solid;
[0018] S5, roasting.
[0019] The room temperature is 15-35℃.
[0020] As an improvement, in step S1, the indium salt is a soluble salt that is soluble in a solvent, and the copper-containing precursor is a soluble substance that is soluble in a solvent. The indium salt can be selected from at least one of indium nitrate, hydrochloride, sulfate, and acetylacetonate, and the solvent is, for example, at least one of water and ethanol. In step S1, the indium salt is first uniformly dispersed in the solvent, and then the copper-containing precursor is added to cooperate with other steps to allow copper to grow uniformly on indium oxide in a doped form.
[0021] As an improvement, in step S2, the surfactant is at least one of hexadecyltrimethylammonium bromide, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate, preferably sodium dodecyl sulfate.
[0022] As an improvement, in step S2, the alkali can be at least one of ammonia, sodium hydroxide, potassium hydroxide, sodium carbonate, and potassium carbonate.
[0023] As an improvement, in step S2, a mixed dispersion B containing surfactant and alkali can be formed by mixing the surfactant with an alkaline solution. The concentration of the alkaline solution is preferably 0.1–10.0 mol / L, for example, 0.5–5 mol / L, and the mass ratio of surfactant to alkaline solution is preferably 1:100–1:20, for example, 1:50–1:20. The alkaline solution is, for example, an aqueous solution of alkali.
[0024] As an improvement, in step S3, the constant temperature is 10–80°C.
[0025] As an improvement, in step S4, the constant temperature is 10–80°C.
[0026] In one implementation, steps S4 and S3 can control the same constant temperature.
[0027] In one embodiment, the reaction can be carried out under the constant temperature condition described in S4, which may involve stirring for 4 to 24 hours at the constant temperature.
[0028] Step S4 involves separation after sufficient temperature control, which can be achieved through filtration or centrifugation (also known as solid-state centrifugation). The separated solids are then washed using a solvent, such as water. Preferably, the washing continues until the pH of the supernatant reaches 7-8. The supernatant refers to the liquid obtained by separating the mixture of washing solvent and solids.
[0029] As an improvement, the calcination atmosphere described in S5 is air, argon, nitrogen, or an atmosphere formed from hydrogen and inactive gases, such as one or more of nitrogen, argon, and helium. In one embodiment, the gas flow rate of the calcination atmosphere is 10 mL / min to 80 mL / min, which is beneficial for controlling the catalyst structure and defect content. Using hydrogen during calcination can increase the defect content. In another embodiment, increasing the hydrogen concentration, increasing the gas flow rate, increasing the calcination temperature, or extending the calcination time can increase the defect content.
[0030] In one embodiment, the calcination described in S5 is carried out at a temperature of 200°C to 600°C, for example, 200°C to 400°C, for a calcination time of 2 hours to 8 hours. The heating rate to the calcination temperature is preferably 2°C to 5°C per minute to prevent catalyst thermal agglomeration. Calcination can begin at any temperature between room temperature and the drying temperature; for example, the dried product can be cooled to room temperature (15°C to 35°C) before being transferred to a calcination furnace for further calcination.
[0031] The roasted product is cooled to room temperature. To prevent rapid cooling and cracking, it is preferable to cool slowly, for example, by natural cooling in the roasting furnace (furnace cooling).
[0032] The present invention further provides a CO2 conversion method, comprising contacting a gas containing CO2 and hydrogen with the aforementioned catalytic material provided by the present invention under light irradiation, wherein the reaction temperature is 200-300°C and the reaction pressure is less than 1.0 MPa, for example 0.1-0.9 MPa.
[0033] The catalyst material provided by this invention is a porous copper-modified indium oxide material with micropores and copper dispersed in the form of doping. As a CO2 conversion catalyst, it can effectively improve the carbon dioxide conversion efficiency under photothermal synergy conditions.
[0034] The catalytic material preparation method provided by this invention can synthesize porous copper-modified indium oxide catalysts, and has at least one of the following beneficial effects, preferably all of them:
[0035] 1. No highly toxic organic solvents are required, and the preparation method is simple and environmentally friendly;
[0036] 2. It uses non-precious metal raw materials, which are inexpensive, have a simple preparation process, good repeatability, and are easy to mass-produce;
[0037] 3. The composition and structure of the resulting catalyst are easy to control;
[0038] 4. The obtained catalyst has a microporous porous structure, which is conducive to promoting the diffusion and migration of CO2, H2 and reaction intermediates, thereby improving the reaction efficiency;
[0039] 5. It allows copper to be highly dispersed in the indium oxide lattice framework in a doped form;
[0040] 6. The obtained catalyst material, as a CO2 conversion catalyst, can effectively improve the carbon dioxide conversion activity under photothermal synergy conditions.
[0041] The CO2 conversion method provided by this invention uses the catalytic material provided by this invention as a catalyst and utilizes the photothermal synergy to improve the catalytic conversion efficiency of carbon dioxide. It can achieve the conversion of carbon dioxide at lower temperatures and lower pressures and has a high CO2 conversion rate.
[0042] The present invention will be further described below with reference to the accompanying drawings and specific embodiments. Attached Figure Description
[0043] Figure 1 This is the X-ray diffraction (XRD) pattern of the porous copper-modified indium oxide prepared in Example 1 for carbon dioxide catalytic conversion.
[0044] Figure 2 This is the Raman spectrum of the porous copper-modified indium oxide prepared in Example 1 for carbon dioxide catalytic conversion.
[0045] Figure 3 The image shown in Example 1 is a transmission electron microscope (TEM) image of porous copper-modified indium oxide prepared for carbon dioxide catalytic conversion. Detailed Implementation
[0046] In the following examples, the micropore and mesopore volumes were determined using the nitrogen adsorption capacity method, see Advanced Materials, 2005, 17(14):1789-1792. The mesopore diameter was calculated using the BJH method, and the mesopore volume is the pore volume of pores with diameters of 2–50 nm.
[0047] In this invention, the gas volume is the volume converted to standard conditions.
[0048] Example 1:
[0049] 50g of indium nitrate was uniformly dispersed in 200mL of water, and then 2g of copper nitrate was added to obtain mixture A. Hexadecyltrimethylammonium bromide was weighed and dispersed in 5.0mol / L ammonia water at a mass ratio of 1:50 (mass ratio of hexadecyltrimethylammonium bromide to ammonia water) to obtain mixed dispersion B. Mixed dispersion B was slowly added to mixture A under constant temperature stirring at 20℃. The pH of the mixture was adjusted to 11, and the reaction was continued for 3 hours. Afterward, the mixture was centrifuged (to separate the solid product), washed until the pH of the supernatant was 7-8, dried, and calcined at 250℃ for 2 hours in a 10% (v / v) H2 / Ar atmosphere (gas flow rate of 40mL / min, H2 gas accounting for 10% (v / v), the remainder being Ar gas). The heating rate from room temperature to the set calcination temperature was 2℃ per minute. After cooling to room temperature, porous copper-modified indium oxide material for carbon dioxide catalytic conversion was obtained. In this example and subsequent examples, the room temperature was 26℃.
[0050] Appendix Figure 1 This is an X-ray diffraction pattern of porous copper-modified indium oxide, showing that the sample mainly exists in the form of indium oxide. (Attached) Figure 2 The image shows the Raman spectrum of porous copper-modified indium oxide, confirming its good crystallinity. (Attached) Figure 3 The transmission electron microscope image shows that the sample has good crystallinity and a rich porous structure.
[0051] The photothermal synergistic catalytic activity of carbon dioxide conversion was tested using a fixed-bed microreactor with a quartz window. The feed gases were H2, CO2, and Ar in a molar ratio of 72:24:4, and the space velocity was 300 mL / min / g catalyst. The catalyst loading was 0.5 g, and the quartz sand content was 4.5 g. The reaction temperature was 200℃~300℃, the reaction pressure was 0.5 MPa, and the light source was a 300W xenon lamp with a light intensity of 200 mW / cm². 2 Sample analysis was performed using chromatography equipped with a flame ionization detector and a thermal conductivity detector. In Example 1, the CO formation rate was 31.0 μmol g at a reaction temperature of 250 °C. -1 h -1 The CH3OH formation rate is 25.6 μmol g. -1 h -1 The selectivity for CH3OH was 45.2%.
[0052] Table 1 shows the test results of the carbon dioxide catalytic reduction performance of porous copper-modified indium oxide materials used for carbon dioxide catalytic conversion.
[0053] Example 2:
[0054] 50g of indium nitrate was uniformly dispersed in 200mL of water, and then 1.5g of copper nitrate was added to obtain mixture A. 3g of hexadecyltrimethylammonium bromide was weighed and dispersed in 4.0mol / L ammonia water at a mass ratio of 1:50 (mass ratio of hexadecyltrimethylammonium bromide to ammonia water) to obtain mixed dispersion B. Mixed dispersion B was slowly added to mixture A under constant temperature stirring at 20℃. The pH of the resulting mixture was adjusted to 11, and the reaction was continued for 3 hours. The resulting solid was then centrifuged (centrifugation of the solid means separating the mixture by centrifugation and obtaining the solid product), washed until the pH of the supernatant was 7-8, and dried. The mixture was calcined at 250℃ for 2 hours in an argon atmosphere (gas flow rate of 40mL / min), with a heating rate (the rate of heating to the calcination temperature) of 2℃ per minute. After cooling to room temperature, the porous copper-modified indium oxide material for carbon dioxide catalytic conversion was obtained. As shown in Table 1, in Example 2, at a reaction temperature of 250℃, the CO generation rate was 32.6 μmol g / L. -1 h -1 The CH3OH formation rate was 29.4 μmol g. -1 h -1 The selectivity for CH3OH was 47.4%.
[0055] Example 3:
[0056] 50g of indium nitrate was uniformly dispersed in 200mL of water, and then 1.5g of copper chloride was added to obtain mixture A. 3g of hexadecyltrimethylammonium bromide was weighed and dispersed in 8.0mol / L ammonia water at a mass ratio of 1:50 to obtain mixed dispersion B. Mixture B was slowly added to mixture A under constant temperature stirring at 20℃. The pH of the resulting mixture was adjusted to 12, and the reaction was continued for 3 hours. The resulting solid was then centrifuged (centrifuging the mixture to separate the solid product), washed until the pH of the supernatant was 7-8, and dried. The mixture was calcined at 300℃ for 4 hours in an argon atmosphere (gas flow rate of 40mL / min) at a heating rate of 2℃ per minute. After cooling to room temperature, the porous copper-modified indium oxide material for carbon dioxide catalytic conversion was obtained. As shown in Table 1, in Example 3, the CO generation rate was 42.1 μmol g / L at a reaction temperature of 250℃. -1 h -1 The CH3OH formation rate is 21.3 μmol g. -1 h -1 The selectivity for CH3OH was 33.6%.
[0057] Example 4:
[0058] 50g of indium nitrate was uniformly dispersed in 200mL of water, and then 2g of copper chloride was added to obtain mixture A. 3g of sodium dodecyl sulfate was weighed and dispersed in a 1.0mol / L sodium hydroxide solution at a mass ratio of 1:20 to obtain mixed dispersion B. Mixed dispersion B was slowly added to mixture A under constant temperature stirring at 20℃. The pH of the resulting mixture was adjusted to 11, and the reaction was continued for 3 hours. The resulting solid was then centrifuged (centrifugation of the solid means separating the mixture by centrifugation and obtaining the solid product), washed until the pH of the supernatant was 7-8, and dried. The mixture was calcined at 250℃ for 2 hours in a 10% H2 / Ar atmosphere (gas flow rate of 40mL / min) with a heating rate of 2℃ per minute. After cooling to room temperature, porous copper-modified indium oxide material for carbon dioxide catalytic conversion was obtained. As shown in Table 1, in Example 4, the CO generation rate was 48.7 μmol g at a reaction temperature of 250℃. -1 h -1 The CH3OH formation rate is 26.2 μmol g. -1 h -1 The selectivity for CH3OH was 35.0%.
[0059] Example 5:
[0060] 50g of indium nitrate was uniformly dispersed in 200mL of water, and then 2g of copper chloride was added to obtain mixture A. 3g of sodium dodecylbenzenesulfonate was weighed and dispersed in a 5.0mol / L sodium hydroxide solution at a mass ratio of 1:50 to obtain mixed dispersion B. Mixed dispersion B was slowly added to mixture A under constant temperature stirring at 20℃. The pH was adjusted to 11, and the reaction was continued for 3 hours. The resulting solid was then centrifuged (centrifuging the mixture to separate the solid product), washed until the pH of the supernatant was 7-8, and dried. The mixture was calcined at 300℃ for 2 hours in an argon atmosphere (gas flow rate of 40mL / min) at a heating rate of 2℃ per minute. After cooling to room temperature, the porous copper-modified indium oxide material for carbon dioxide catalytic conversion was obtained. As shown in Table 1, in Example 5, the CO generation rate was 36.8 μmol g at a reaction temperature of 250℃. -1 h -1 The CH3OH formation rate is 27.0 μmol g. -1 h -1 The selectivity for CH3OH was 42.3%.
[0061] Example 6:
[0062] 50g of indium nitrate was uniformly dispersed in 200mL of water, and then 2g of copper chloride was added to obtain mixture A. 3g of sodium dodecylbenzenesulfonate was weighed and dispersed in a 5.0mol / L sodium hydroxide solution at a mass ratio of 1:50 to obtain mixed dispersion B. Mixed dispersion B was slowly added to mixture A under constant temperature stirring at 20℃. The pH of the mixture was adjusted to 11, and the reaction was continued for 5 hours. The resulting solid was then centrifuged, washed until the pH reached 7-8, and dried. It was calcined at 500℃ for 2 hours in a 10% H2 / Ar atmosphere (gas flow rate of 40mL / min) with a heating rate of 2℃ per minute. After cooling to room temperature, the porous copper-modified indium oxide material for carbon dioxide catalytic conversion was obtained. As shown in Table 1, in Example 5, the CO generation rate was 39.9 μmol g at a reaction temperature of 250℃. -1 h -1 The CH3OH formation rate is 28.1 μmol g. -1 h -1 The selectivity for CH3OH was 41.3%.
[0063] Comparative Example 1:
[0064] 50 g of indium nitrate was uniformly dispersed in 200 mL of water to obtain mixture A. Hexadecyltrimethylammonium bromide was weighed and dispersed in 5.0 mol / L ammonia water at a mass ratio of 1:50 to obtain mixed dispersion B. Mixed dispersion B was slowly added to mixture A under constant temperature stirring at 20 °C. The pH of the mixture was adjusted to 11, and the reaction was continued for 3 hours. The resulting solid was centrifuged (centrifugation of the solid product means separating the mixture by centrifugation), washed until the pH of the supernatant was 7–8, and then dried. The mixture was calcined at 250 °C for 2 hours in a 10 v / v H₂ / Ar atmosphere (gas flow rate of 40 mL / min), with a heating rate of 2 °C per minute to the calcination temperature. After cooling to room temperature, the catalyst of Comparative Example 1 was obtained. As shown in Appendix Table 1, in Comparative Example 1, the CO formation rate was 8.2 μmol g / L at a reaction temperature of 250 °C. -1 h -1 The CH3OH formation rate is 0.9 μmol g. - 1 h -1 The selectivity for CH3OH was 9.9%.
[0065] Comparative Example 2:
[0066] 50g of indium nitrate was uniformly dispersed in 200mL of water to obtain mixture A; 3g of hexadecyltrimethylammonium bromide was weighed and dispersed in 4.0mol / L ammonia water at a mass ratio of 1:50 to obtain mixed dispersion B; mixed dispersion B was slowly added to mixture A under constant temperature stirring at 20℃, the pH of the mixture was adjusted to 11, and the reaction was continued for 3 hours. The resulting solid was centrifuged (centrifugation of the obtained solid means centrifuging the mixture to separate it and obtain the solid product), washed until the pH of the supernatant was 7-8, and dried. The mixture was calcined at 250℃ for 2 hours in an argon atmosphere (gas flow rate of 40mL / min) at a heating rate of 2℃ per minute, and cooled to room temperature to obtain Comparative Example 2. As shown in Appendix Table 1, in Comparative Example 2, the CO generation rate was 6.8 μmol g at a reaction temperature of 250℃. -1 h -1 The CH3OH formation rate is 1.4 μmol g. -1 h -1 The selectivity for CH3OH was 17.1%.
[0067] Comparative Example 3:
[0068] 50g of indium nitrate was uniformly dispersed in 200mL of water to obtain mixture A. 3g of hexadecyltrimethylammonium bromide was weighed and dispersed in 4.0mol / L ammonia water at a mass ratio of 1:50 (mass ratio of hexadecyltrimethylammonium bromide to ammonia water) to obtain dispersion B. Dispersion B was slowly added to mixture A under constant temperature stirring at 20℃. The pH of the resulting mixture was adjusted to 11, and the reaction was continued for 3 hours. The resulting solid was then centrifuged (centrifugation separates the mixture and obtains the solid product), washed until the pH of the supernatant reached 7-8, and dried. The mixture was calcined at 250℃ for 2 hours under an argon atmosphere (gas flow rate of 40mL / min) with a heating rate of 2℃ per minute. After cooling to room temperature, pure indium oxide without copper was obtained. The obtained indium oxide was dispersed in 10mL of water, and 1.5g of copper nitrate was added. The mixture was then dried by rotary evaporation at 81℃. The sample was calcined at 250°C for 2 hours in an argon atmosphere (gas flow rate of 40 mL / min) with a heating rate of 2°C per minute. After cooling to room temperature, Comparative Example 3 was obtained. As shown in Table 1, in Comparative Example 3, the CO formation rate was 8.0 μmol g at a reaction temperature of 250°C. -1 h -1 The CH3OH formation rate is 2.0 μmol g. -1 h -1 The selectivity for CH3OH was 20.0%.
[0069] Comparative Example 4:
[0070] 50g of indium nitrate was uniformly dispersed in 200mL of water, and then 2g of copper nitrate was added to obtain mixture A. Ammonia solution with a concentration of 5.0mol / L was slowly added to mixture A, and the pH of the mixture was adjusted to 11. After stirring for 3 hours, the mixture was centrifuged (centrifuging the obtained solids separates the mixture and obtains the solid product). The mixture was washed until the pH of the supernatant was 7-8, dried, and calcined at 250℃ for 2 hours in a 10% (v / v) H2 / Ar atmosphere (gas flow rate of 40mL / min). The heating rate from room temperature to the set temperature was 2℃ per minute. After cooling to room temperature, Comparative Example 4 was obtained. As shown in Table 1, in Comparative Example 4, the CO generation rate was 8.0 μmol g / L at a reaction temperature of 250℃. -1 h -1 The CH3OH formation rate is 2.0 μmol g. -1 h -1 The selectivity for CH3OH was 20.0%.
[0071] Table 1
[0072]
[0073] In Table 1, V 微孔 V is the pore volume of pores with a diameter of less than 2 nm. 介孔 It is the pore volume of a pore with a diameter of 2-5 nm.
Claims
1. A catalytic material for the catalytic conversion of carbon dioxide, comprising indium oxide and a copper-doped modification element, having a rich porous structure, wherein the copper content is 0.5% to 8% by weight, and the indium oxide content is 92% to 99.5% by weight; the catalytic material has 1-5 nm micropores with a micropore volume of 0.005 to 0.03 cm³. 3 ·g –1 The mesopore volume is 0.1~0.4 cm³. 3 ·g –1 ; The preparation method of the catalytic material includes the following steps: S1. After uniformly dispersing the indium salt in the solvent, a copper-containing precursor is added to obtain mixture A; S2. Prepare a mixed dispersion B containing a surfactant and an alkali; the surfactant is one or more of hexadecyltrimethylammonium bromide, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate. S3. Under constant temperature conditions, add the mixed dispersion B to the mixture A, and control the pH value of the resulting mixture to be 11~13; S4. React completely at a constant temperature, separate, wash and dry the resulting solid; S5, roasting; The carbon dioxide catalytic conversion includes: contacting a gas containing CO2 and hydrogen with the catalytic material for reaction, wherein the reaction temperature is 200-300℃, the reaction pressure is less than 1.0 MPa, and the reaction is carried out under light irradiation.
2. The catalytic material according to claim 1, characterized in that, Copper is highly dispersed in the indium oxide lattice framework in the form of dopants.
3. The catalytic material according to claim 1, characterized in that, The copper content is 1-5% by weight, the indium oxide content is 95-99% by weight, and the micropore volume is 0.01-0.02 cm³. 3 ·g –1 Mesopore volume: 0.15~0.35 cm³ 3 ·g –1 .
4. A method for preparing the catalytic material for carbon dioxide catalytic conversion as described in claim 1, comprising the following steps: S1. After uniformly dispersing the indium salt in the solvent, a copper-containing precursor is added to obtain mixture A; S2. Prepare a mixed dispersion B containing a surfactant and an alkali; the surfactant is one or more of hexadecyltrimethylammonium bromide, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate. S3. Under constant temperature conditions, add the mixed dispersion B to the mixture A, and control the pH value of the resulting mixture to be 11~13; S4. React completely at a constant temperature, separate, wash and dry the resulting solid; S5, roasting.
5. The method according to claim 4, characterized in that, In step S1, the indium salt is one or more of indium nitrate, indium hydrochloride, indium sulfate, and indium acetylacetonate; the copper-containing precursor is one or more of copper chloride, copper nitrate, copper sulfate, and copper acetylacetonate; and the solvent is water and / or ethanol.
6. The method according to claim 4, characterized in that, The alkali is one or more of ammonia, sodium hydroxide, and potassium hydroxide.
7. The method according to claim 4, characterized in that, In step S2, the mixed dispersion B is formed by mixing an alkaline solution and a surfactant; the concentration of alkali in the alkaline solution is 0.1~5.0 mol / L, and the mass ratio of surfactant to alkaline solution is 1:100~1:
20.
8. The method according to claim 4, characterized in that, In step S3, the constant temperature is 10~80℃.
9. The method according to claim 4, characterized in that, In step S4, the constant temperature is 10~80℃; the washing is performed until the pH value of the supernatant is 7~8.
10. The method according to claim 4, characterized in that, In step S5, the calcination atmosphere is one or more of air, argon, or nitrogen, or an atmosphere formed by hydrogen and an inactive gas. The calcination temperature is 200℃~600℃, the time is 2 hours~8 hours, and the heating rate to the calcination temperature is 2℃~5℃ per minute.
11. The method according to claim 10, characterized in that, In step S5, the flow rate of the calcining atmosphere gas is 10 mL / min to 80 mL / min, and the separation in step S4 is centrifugal separation.
12. The catalytic material prepared by the method of any one of claims 4–11.
13. The application of the catalytic material according to any one of claims 1-3 or claim 12 in CO2 conversion, wherein the application is carried out under light irradiation and the reaction pressure is less than 1.0 MPa.
14. A CO2 conversion method, comprising reacting a gas containing CO2 and hydrogen with a catalytic material according to any one of claims 1-3 or claim 12, wherein, The reaction temperature is 200-300℃, the reaction pressure is less than 1.0 MPa, and the reaction is carried out under light irradiation.
Citation Information
Patent Citations
Indium oxide catalyst and preparation method and application thereof
CN110479235A
Preparation method for indium oxide sequential nano mesoporous materials doping with metal
CN102642863A
Black ultrathin indium oxide nanosheet, and preparation method and photothermal catalysis application thereof
CN109647373A